Оптимізація діяльності інтернет-магазину - Зоц, Леонід; Комова, Марія (Видавництво Львівської політехніки, 2020)
This article analyzes the work of an online store. The functions and speed of the site are checked. The criteria for improving the operation of the store are given. Optimization programs and site verification services are analyzed.
Keywords: Інтернет-магазин; програми оптимізації; сервіси; швидкіть завантаження